2015
DOI: 10.1111/jop.12399
|View full text |Cite
|
Sign up to set email alerts
|

Declined hTERT expression of peripheral blood CD4+ T cells in oral lichen planus correlated with clinical parameter

Abstract: A divergent hTERT pattern between CD4(+) and CD8(+) T cells was implicated in OLP. Decreased hTERT in CD4(+) T cells might be responsible for the immune dysfunction in OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Most studies investigating telomerase in autoimmune diseases have found increased telomerase activity or hTERT gene expression in disease versus healthy states (Katayama and Kohriyama, 2001;Kurosaka et al, 2001;Kurosaka et al, 2003;Kurosaka et al, 2006;Qi et al, 2013;Tarhan et al, 2008;Wu et al, 2000;Wu et al, 1999a;Yudoh et al, 1999). However, one study observed no difference (Vazirpanah et al, 2017) and two studies reported lower hTERT mRNA expression in patients compared to healthy controls (Tarhan et al, 2008;Zhang et al, 2016). Interestingly, differences in telomerase activity were observed between active and inactive disease (Katayama and Kohriyama, 2001), probably due to changes in inflammatory and oxidative stress levels.…”
Section: Autoimmune Disease and Telomerasementioning
confidence: 99%
“…Most studies investigating telomerase in autoimmune diseases have found increased telomerase activity or hTERT gene expression in disease versus healthy states (Katayama and Kohriyama, 2001;Kurosaka et al, 2001;Kurosaka et al, 2003;Kurosaka et al, 2006;Qi et al, 2013;Tarhan et al, 2008;Wu et al, 2000;Wu et al, 1999a;Yudoh et al, 1999). However, one study observed no difference (Vazirpanah et al, 2017) and two studies reported lower hTERT mRNA expression in patients compared to healthy controls (Tarhan et al, 2008;Zhang et al, 2016). Interestingly, differences in telomerase activity were observed between active and inactive disease (Katayama and Kohriyama, 2001), probably due to changes in inflammatory and oxidative stress levels.…”
Section: Autoimmune Disease and Telomerasementioning
confidence: 99%
“…The OLP patients were diagnosed according to the clinicopathologically modified WHO diagnostic criteria of OLP. 18 The exclusion criteria were as follows: cases with the age below 18 or above 70 years old; pregnant women; patients who suffered from oral lesions adjacent to metal crowns or amalgam fillings; individuals with other detectable oral lesions or systemic diseases, or received treatment 3 months before the sample collection. Patients receiving any medication that can cause lichenoid reactions such as antihypertensive drugs and oral hypoglycemics were also excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies investigating telomerase in autoimmune diseases have found increased telomerase activity or hTERT gene expression in disease versus healthy states (Katayama and Kohriyama, 2001;Kurosaka et al, 2001;Kurosaka et al, 2003;Kurosaka et al, 2006;Qi et al, 2013;Tarhan et al, 2008;Wu et al, 2000;Wu et al, 1999a;Yudoh et al, 1999). However, one study observed no difference (Vazirpanah et al, 2017) and two studies reported lower hTERT mRNA expression in patients compared to healthy controls (Tarhan et al, 2008;Zhang et al, 2016). Interestingly, differences in telomerase activity were observed between active and inactive disease (Katayama and Kohriyama, 2001), probably due to changes in inflammatory and oxidative stress levels.…”
Section: Autoimmune Disease and Telomerasementioning
confidence: 99%